An analysis of data on Sokoto Gudali cattle at Bulassa and Dogondaji, north western state, Nigeria - Wheat, J.D.; Broadhurst, J. (1972)
Growth performance of Sokoto Gudali was investigated at Bulussa and Dogondaji, Nigeria. Animal weights at different ages were examined. Data on influence of sire, sex and month of birth, dates of age at first calving and calving interval included.